The relationship between religiosity leadership style and business performance of muslim small and medium enterprise-micro (smes) - Mohd Ali, Nor Atikah; Mohamed Elias, Ezanee (Universiti Utara Malaysia, 2020)
In this paper a new instrument measuring Islamic role in religiosity leadership style is presented. The objective of the study is to investigate the role of religiosity leadership style in business performance among the management of micro small and medium enterprises operated by Muslim entrepreneurs. Right now, leadership style is one of basic components for organizational leaders in leading the company, planning business directions, executing vital plans and inspiring workers. Currently, the centrality of leadership is not exclusively being impacted by participative or transformational leadership. In-fact the direction from religiosity leadership is similarly significant. For the most part, leadership is generally influenced by individual’s religiosity style in the management. Based on previous study, these factors contribute to a significant research gap in terms of religiosity leadership’s style in the managerial practices of Muslim SMEs towards business performance. Hence, the study has constructed a theoretical framework to observe the impact of religiosity leadership style on Muslim SMEs’ business performance. A quantitative design with simple random sampling using structured survey questionnaires will be distributed to 100 Muslim SMEs. The data were evaluated using SPSS. The results of the study indicate that the religiosity leadership has mixed results. In this unique situation, religiosity leadership makes a substantial contribution to Muslim SMEs by enhancing business performance in certain market segments.